On the behavior of monopiles subjected to multiple episodes of cyclic loading and reconsolidation in cohesive soils. (June 2021) - Duque, J.; Ochmański, M.; Mašín, D.; Hong, Y.; Wang, L.
Abstract: The study of cyclic loading on saturated natural clay deposits is of great interest for the analysis of offshore and onshore structures. Recent experimental research in the field of offshore engineering has indicated that the mechanical behavior of monopiles is strongly influenced by the reconsolidation processes that take place during calm conditions. After the reconsolidation episodes, the soil-pile stiffness considerably increases. Unfortunately, the previous behavior is usually disregarded in the numerical analysis and design of monopiles. In this work, the behavior of monopiles subjected to multiple episodes of cyclic loading and reconsolidation is analyzed from a numerical point of view. For that purpose, the sophisticated hypoplastic model for clays by Mašín (2014) with intergranular strain by Niemunis and Herle (1997) is carefully evaluated under element test conditions and by back-calculating some centrifuge tests. For the calibration of the constitutive model, three undrained monotonic and three undrained cyclic triaxial tests were performed. At the end, the influence of reconsolidation stages on the design of monopiles and the model capabilities to reproduce this behavior are discussed.